A LITERATURE REVIEW: THE EFFECT OF HONEY IN PRESSURE ULCERWOUND HEALING ACCELERATION - Ariani, Yuni; Aliyatur, Titin; Wicaksono, Bambang (Jurnal Rekonstruksi dan Estetik, 2022)
HIGHLIGHTS: 1. Honey dressings can accelerate wound healing in patients with pressure ulcers.2. Honey-soaked gauze can provide quicker pain relief and reduce discomfort during dressing changes compared to other topical dressings.   ABSTRACT: Background: Pressure ulcers occur due to prolonged pressure and friction in areas of bony prominences that result in tissue injury with varying depths. To date, there is no standardized wound dressing for these ulcers. From the review of the availability and affordability aspects, honey can be used as a wound dressing because it contains anti-oxidants, anti-inflammatory, and anti-bacterial properties. This article investigates the advantages of honey dressing over other modern dressings. Methods: Literature search from online databases using relevant keywords. A total of three articles were discussed in this review article. Results: All articles agreed that giving honey to pressure ulcer wounds reduced wound size and pain. Honey-soaked gauze provided quicker pain relief during treatment and reduced discomfort with each dressing change. Wound healing was proven to be four times faster with honey compared to other topical dressings. The anti-bacterial effect of honey could not be significantly confirmed in this study. Nonetheless, honey dressings succeeded in accelerating wound healing in patients with pressure ulcers. Conclusion: Honey can be a promising alternative to topical dressings in patients with pressure ulcers.